3D solid robot animation design based on ADAMS - Baojian Yang; Yongning Deng; Xia Yue; Tze, Kenneth Kin Teo (Springer, 2023)
The rapid development of science and technology promotes the intensive development of robotics and the application of ADAMS in the field of robotics is constantly expanding. Research on robot kinematics and dynamics is the core issue of biped robot animation simulation. It is of great significance to propose an efficient and improved inverse kinematics algorithm for the development of robotic bionics in China. In this paper, the BIOLOID robot assembly kit is used as the research platform. Based on this, the biped robot kinematics equations and dynamic equations are deduced, and a three-step programming method is used to carry out reasonable gait planning for the biped robot. A simplified virtual prototype model of the lower limb of a biped robot, and the motion trajectories of the joints are input to perform motion simulation of the robot’s static walking. The feasibility of gait planning is verified by analyzing the dynamic images obtained from the simulation experiments and the experimental data of each joint vector. This paper uses the Denavit-Hartenberg rule to construct a biped robot animation simulation kinematics model, deduces a matrix expression describing joint vectors between adjacent links, and solves the biped robot’s positive kinematics equation by chain multiplication rule; An efficient and improved inverse kinematics algorithm is proposed. This solution has the characteristics of high accuracy, high efficiency and few redundant solutions. The experimental study found that the three-step planning method for biped robotic static walking planning is feasible and can reach 98%, and can meet the pre-planning requirements.